A French collaborative survey of 272 fetuses with 22q11.2 deletion: ultrasound findings, fetal autopsies and pregnancy outcomes. (12th February 2014) - Besseau‐Ayasse, J.; Violle‐Poirsier, C.; Bazin, A.; Gruchy, N.; Moncla, A.; Girard, F.; Till, M.; Mugneret, F.; Coussement, A.; Pelluard, F.; Jimenez, M.; Vago, P.; et al.
ABSTRACT Objective The 22q11.2 deletion (del22q11.2) is one of the most common microdeletions. We performed a collaborative, retrospective analysis in France of prenatal diagnoses and outcomes of fetuses carrying the del22q11.2. Methods A total of 272 fetuses were included. Data on prenatal diagnosis, ultrasound findings, pathological features, outcomes and inheritance were analyzed. Results The mean time of prenatal diagnosis was 25.6 ± 6 weeks of gestation. Most of the diagnoses (86.8%) were prompted by abnormal ultrasound findings [heart defects (HDs), in 83.8% of cases]. On fetal autopsy, HDs were again the most common disease feature, but thymus, kidney abnormalities and facial dysmorphism were also described. The deletion was inherited in 27% of cases. Termination of pregnancy (TOP) occurred in 68.9% of cases and did not appear to depend on the inheritance status. However, early diagnosis was associated with a higher TOP rate. Conclusion This is the largest cohort of prenatal del22q11.2 diagnoses. As in postnatally diagnosed cases, HDs were the most frequently observed abnormalities. However, thymus and kidney abnormalities and polyhydramnios should also be screened for in the prenatal diagnosis of del22q11.2. Only the time of diagnosis appeared to be strongly associated with the pregnancy outcome: the earlier the diagnosis, the higher the TOP rate. © 2014 John Wiley & Sons, Ltd.